2007
DOI: 10.1016/j.clay.2006.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of benzoic acid by CTAB exchanged montmorillonite

Abstract: This paper reports the adsorption of benzoic acid from water on cetyl trimethylammonium exchanged montmorillonite (CTAB-montmorillonite). Important factors are the adsorbent concentration, ionic strength, equilibrium time and pH. The largest adsorption is at pH 9. The adsorption kinetics data fitted the pseudo-second-order equation. The adsorption isotherms at different pH were linear indicating a partition mechanism. Up to about 61% of the dissolved benzoic acid was adsorbed by CTAB-montmorillonite. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 23 publications
1
23
0
2
Order By: Relevance
“…The montmorillonite has also been proved to be suitable host clay material for the controlled syntheses of catalytically active transition metal particles [32,35,46]. Unlike commonly reported microporous pillared structure, a TiO 2 cluster structure in the present study was observed, the purified montmorillonite was firstly modified by cetyltrimethylammonium bromide (CTAB) through an ion-exchange reaction [40,47]. The basal spacing was further expanded by the intercalation of dodecylamine (DDA), and then TiO 2 was dispersed and attached in the structure and surface of montmorillonite by hydrolyzing TiO(OH) 2 sol using Ti(OC 4 H 9 ) 4 as the precursor.…”
Section: Formation Mechanisms Of Tio 2 Nanoparticles and Tio 2 /Montmmentioning
confidence: 76%
See 3 more Smart Citations
“…The montmorillonite has also been proved to be suitable host clay material for the controlled syntheses of catalytically active transition metal particles [32,35,46]. Unlike commonly reported microporous pillared structure, a TiO 2 cluster structure in the present study was observed, the purified montmorillonite was firstly modified by cetyltrimethylammonium bromide (CTAB) through an ion-exchange reaction [40,47]. The basal spacing was further expanded by the intercalation of dodecylamine (DDA), and then TiO 2 was dispersed and attached in the structure and surface of montmorillonite by hydrolyzing TiO(OH) 2 sol using Ti(OC 4 H 9 ) 4 as the precursor.…”
Section: Formation Mechanisms Of Tio 2 Nanoparticles and Tio 2 /Montmmentioning
confidence: 76%
“…The possible formation mechanism of mesoporous TiO 2 /montmorillonite includes the intercalated quaternary ammonium cations and neutral amines as co-surfactants to direct the interlamellar hydrolysis and condensation polymerization of neutral inorganic precursor [32,40,41,46]. Thus the pore size becomes controllable, and the thermal stability is improved.…”
Section: Formation Mechanisms Of Tio 2 Nanoparticles and Tio 2 /Montmmentioning
confidence: 99%
See 2 more Smart Citations
“…[20,21] Due to their highly specific surface area, high cationic exchange capacity (CEC), and high abundance and resulting low price, clay minerals can be used as effective, environmentally friendly adsorbents for metal ions. The adsorption capacity and character of the clay minerals have been modified by treatment with sulfuric acid [22] and humic acid, [23] as well as by immobilization of anionic [24] and cationic [25,26] surfactants. Replacement of natural exchangeable cations with cationic surfactant makes the clay mineral surface more hydrophobic.…”
Section: Introductionmentioning
confidence: 99%